2016
DOI: 10.1007/s10571-016-0412-x
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Attenuates Ischemia/Reperfusion-Induced Hippocampal Neurons Injury Via Akt-nNOS-JNK Signaling Pathway

Abstract: Ischemia-induced brain damage leads to apoptosis like delayed neuronal death in selectively vulnerable regions, which could further result in irreversible damages. Previous studies have demonstrated that neurons in the CA1 area of hippocampus are particularly sensitive to ischemic damage. Atorvastatin (ATV) has been reported to attenuate cognitive deficits after stroke, but precise mechanism for neuroprotection remains unknown. Therefore, the aims of this study were to investigate the neuroprotective mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Furthermore, another explanation can be led by the upregulation of p -Akt, where Shao et al (2016) reported that administration of LY294002, a PI3K inhibitor, reversed the hippocampal protective effect of atorvastatin, another HMG-CoA reductase suppressor, through the inhibition of p -Akt and the upregulation of p -JNK3, suggesting the inverse correlation between the two molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, another explanation can be led by the upregulation of p -Akt, where Shao et al (2016) reported that administration of LY294002, a PI3K inhibitor, reversed the hippocampal protective effect of atorvastatin, another HMG-CoA reductase suppressor, through the inhibition of p -Akt and the upregulation of p -JNK3, suggesting the inverse correlation between the two molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from their destructive role, ROS/RNS initiate apoptotic signaling pathways, such as JNK3 ( Hu et al, 2012 ), which is an important subclass of the mitogen-activated protein kinase family ( Meloni et al, 2014 ). Activated JNK3 aggravates ischemia-induced apoptotic signaling by promoting the expression/activity of crucial proteins involved in apoptosis, such as c-Jun, Bcl-2 associated X protein (Bax), and caspase-3 ( Hetz et al, 2005 ; Shao et al, 2016 ). Hence, inhibition of JNK3 shows a neuroprotective effects against several models of cerebral I/R injury ( Ge et al, 2017 ; Luo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…All of these protective effects of atorvastatin are reversed by LY294002 [an inhibitor of phosphatidylinositide 3-kinase (PI3K)]. Pretreatment with JNK inhibitor SP600125 diminishes the phosphorylation of JNK3 and c-Jun, and further inhibits the activation of caspase-3 after cerebral ischemia/reperfusion (Shao et al, 2017 ).…”
Section: Effects Of Modulation Of Jnk Activitymentioning
confidence: 99%
“…Ischemia/reperfusion suppresses Akt/nNOS pathway, leading to the activation of JNK3 and induction of apoptosis. In this context, atorvastatin pre-treatment prevents the reduction in Akt phosphorylation mediated by ischemic damage and promotes survival in hippocampal neurons [308]. Statin-mediated neuroprotection in stroke may be also exerted by immunomodulatory actions.…”
Section: Statins and Strokementioning
confidence: 99%